Recent developments in catalyst synthesis using DBD plasma for reforming applications. (26th April 2021) - Khoja, Asif Hussain; Mazhar, Arslan; Saleem, Faisal; Mehran, Muhammad Taqi; Naqvi, Salman Raza; Anwar, Mustafa; Shakir, Sehar; Saidina Amin, Nor Aishah; Sajid, Muhammad Bilal
Abstract: The catalyst has a significant role in gas processing applications such as reforming technologies for H2 and syngas production. The stable catalyst is requisite for any industrial catalysis application to make it commercially viable. Several methods are employed to synthesize the catalysts. However, there is still a challenge to achieve a controlled morphology and pure catalyst which majorly influences the catalytic activity in reforming applications. The conventional methods are expansive, and the removal of the impurities are major challenges. Nevertheless, it is not straightforward to achieve the desired structure and stability. Therefore, significant interest has been developed on the advanced techniques to take control of the physicochemical properties of the catalyst through non-thermal plasma (NTP) techniques. In this review, the systematic evolution of the catalyst synthesis using NTP technique is elucidated. The emerging DBD plasma to synthesized and effective surface treatment is reviewed. DBD plasma synthesized catalyst performance in reforming application for H2 and syngas production is summarised. Furthermore, the status of DBD plasma for catalyst synthesis and proposed future avenues to design environmentally suitable and cost-effective synthesis techniques are discussed. Graphical abstract: Image 1 Highlights: The NTP plasma techniques for catalyst synthesis is overviewed. The DBD plasma-treated catalyst is summarised. Prospects of DBD for catalyst synthesis in H2 /syngas production is presented.